2013
DOI: 10.29309/tpmj/2013.20.02.685
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Amputation;

Abstract: Amputation is stated to be a foremost but preventable community health problem causing intense financial, social andemotional effects on the patient and family particularly in developing countries where the prosthetic services are limited. The purpose ofthis study was to identify the causes and levels of amputation in low resource community, Sindh Pakistan. Methods: This was aretrospective chart review study that was carried out at first civilian Institute of physical medicine & rehabilitation-Dow Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Each of these considerations would play a role in the decision to ablate the limb at a specific level with a varying weight depending on the clinical situation ( 10 ). In descending order, the patterns of LA in low income countries were trans-tibial, trans-femoral, trans-radial and trans-humeral ( 11 ). The majority of amputee patients in developed countries were over 60 years old, and vascular issues accounted for 80-90% of LEA ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these considerations would play a role in the decision to ablate the limb at a specific level with a varying weight depending on the clinical situation ( 10 ). In descending order, the patterns of LA in low income countries were trans-tibial, trans-femoral, trans-radial and trans-humeral ( 11 ). The majority of amputee patients in developed countries were over 60 years old, and vascular issues accounted for 80-90% of LEA ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…They believe in themselves (Nathawat & Mathur, 1993). Higher job prospects, higher qualifications (Del Mar Salinas-Jiménez et al, 2011) and financial status help develop self-esteem (McMullin & Cairney, 2004;Zeab 2015;Rehman, 2019;Al-Qahtani, 2021, Jayachitra andJagannarayan, 2021), self-efficacy (Bharvad, 2016) better subjective well-being (Del Mar Salinas-Jiménez et al, 2013;Soomro et al, 2013;Singh, 2014). A study by Shaheen (2015) found a correlation between overall life and psychological well-being, indicating higher satisfaction with life, optimism, and psychological well-being among employed women when compared with homemakers.…”
Section: Introductionmentioning
confidence: 99%